Subtract <math><mstyle displaystyle="true"><mn>2</mn><mi>x</mi></mstyle></math> from both sides of the equation.

Divide each term in <math><mstyle displaystyle="true"><mn>3</mn><mi>y</mi><mo>=</mo><mn>12</mn><mo>-</mo><mn>2</mn><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Simplify each term.

Divide <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Move the negative in front of the fraction.

Do you know how to Solve for y 2x+3y=12 for y? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.